Unveiling Geobacter sulfurreducens electron transfer chain: probing the mechanisms of bacterial electricity production - Teixeira, Liliana Patrícia dos Reis (2022)
Geobacter bacteria have been gaining attention due to their biotechnological and bioremediation applications. Species like G. sulfurreducens are capable of bioenergy production and removal of contaminants from wastewaters. G. sulfurreducens is capable of transferring electrons towards extracellular acceptors, in a process called extracellular electron transfer, and it is also capable of accepting electrons in current consuming biofilms. In order to take full advantage of their applications, it is necessary to understand the mechanisms and the proteins involved in these processes. G. sulfurreducens genome encodes for more than 100 c-type cytochromes, being these the main intervenient in the electron transfer. In this thesis, some of the cytochromes encoded by this bacterium were studied: OmcF, and outer-membrane monoheme cytochrome, PpcA, a thriheme periplasmatic cytochrome, and PccH and GSU2515, both monoheme cytochromes localized at the periplasm. Using Nuclear Magnetic Resonance (NMR) was possible to assign the backbone and side-chain of OmcF in the oxidized state, and use these results to perform molecular interactions with PpcA. Although the results of the interaction were inconclusive, the assignment of OmcF constitutes an important step to find putative redox partners of this protein. Using cyclic voltammetry, an electrochemical study was performed on OmcF. Furthermore, by constructing strategic mutants, analyzing their NMR spectra and determining their redox potential, was possible to determine the redox-Bohr center of OmcF. NMR spectroscopy was also used to assign the backbone, side-chain and heme substituents of PccH in the oxidized state. A biochemical and structural characterization of cytochrome GSU2515 was carried using circular dichroism, visible redox titrations, UV-visible, and NMR spectroscopy techniques. By performing NMR molecular interactions between GSU2515 and PccH, there is a strong indication that these two cytochromes are physiological partners. The results obtained contribute to a better understanding of the electron transfer mechanisms of G. sulfurreducens.